Inventory Management Literacy, Information Technology Adoption and MSME Operational Efficiency: The Role of Inventory Control Mediation - Enggar Nursasi; Hadiana Fernanda (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to examine the effect of inventory management literacy (LMP) and information technology adoption (ATI) on the operational efficiency (EO) of SMEs, with inventory control (PP) as a mediating variable. A quantitative approach with an explanatory survey design was employed, involving 120 SME owners/managers selected through purposive sampling and analyzed using PLS-SEM with SmartPLS 4.0. The results show that LMP and ATI each have a significant positive direct effect on both PP and EO, with ATI being the strongest predictor of PP. PP also has a significant positive effect on EO and partially mediates both the ATI-EO and LMP-EO relationships. The model demonstrates substantial predictive power in explaining variance in EO. These findings confirm that improving inventory management literacy and IT adoption are important strategies for SMEs to enhance operational efficiency, both directly and through strengthening their inventory control systems